Rationale for investigating the use of anifrolumab in neuropsychiatric systemic lupus erythematosus: a combined narrative and case-based systematic literature review - Chessa, Elisabetta; Congiu, Fabio; Rizzo, Giulia; Pireddu, Marta Paola; Ragusa, Elena; Floris, Alberto; Cauli, Alberto; Piga, Matteo (Frontiers in Immunology, 2026)
BackgroundNeuropsychiatric (NP) involvement represents one of the major challenges in Systemic Lupus Erythematosus (SLE), often requiring individualized therapeutic strategies. While anifrolumab inhibits the type I interferon receptor 1 (IFNAR1) and is approved for the treatment of moderate-to-severe SLE, randomized controlled trials have not evaluated its efficacy in NPSLE.MethodsWe examined the pathophysiological rationale for inhibiting IFN-α using anifrolumab in NPSLE. To supplement this, we report an original case of NPSLE successfully treated with anifrolumab, along with similar cases identified through a systematic literature review (SLR) of Medline/PubMed and Embase, performed in accordance with PRISMA and CABARET guidelines.ResultsOverexpression of IFN-α is linked to neurological symptoms in patients with inflammatory NPSLE, such as psychosis and seizures. Blocking the IFNAR1 with anifrolumab provides a direct rationale for treating this subset of NPSLE. The SLR identified seven case reports of female patients with inflammatory NPSLE where anifrolumab was used as a rescue therapy following conventional treatment failure. NPSLE manifestations were heterogeneous, including psychosis, headache, and acute confusional state, which limits the generalizability of our findings. A 52-year-old female with SLE and seizures from our Lupus Clinic who received anifrolumab after failing multiple treatments was also reported. After an average of 11.7 months, all patients showed improvement, 87% (7 out 8) achieving complete NP symptom resolution and 62% reaching SLE remission. No emerging safety issues were reported.ConclusionPreliminary observations suggest a potential benefit of anifrolumab in NPSLE, but evidence remains insufficient to establish clinical efficacy and warrants further controlled studies.